A Temporary Haven: Jewish World War II Refugee Scholars at the New York Public Library, 1933–1945 - Intrator, Miriam (Österreichische Zeitschrift für Geschichtswissenschaften, 2010)
The Humanities Research Library of the New York Public Library (NYPL) served as temporary employer and safe intellectual haven for a number of European refugee scholars fleeing Nazism. The closed-stack public library, dedicated to research and the development and documentation of comprehensive scholarly collections, more closely resembled European academic and library systems than did most, more informal, American colleges and universities. As such, NYPL, in conjunction with the Emergency Committee in Aid of Displaced Foreign Scholars, provided a welcome point of transition and life-saving and sustaining work and salaries for the newly arrived refugees who were able to secure some continuity with their pre-war intellectual lives within its walls.